2018
DOI: 10.1097/jnn.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances and Signs of Approaching Death in Patients With Amyotrophic Lateral Sclerosis Undergoing Noninvasive Ventilation in Home Care Settings

Abstract: The purpose of this study was to elucidate the circumstances and symptoms of patients with amyotrophic lateral sclerosis (ALS) using noninvasive positive pressure ventilation (NPPV) in whom death was approaching, to understand how to provide palliative care to dying patients with ALS receiving NPPV management. The participants were 6 home visiting nurses who were head or subhead nurses of a home visiting nursing agency. Data were collected conducting individual semistructured interviews and then group intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The review identified 31 documents (see Table S1 ) from those 19 papers reporting empirical research, of which 11 used quantitative methods [ 11 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and 8 used qualitative methods [ 13 , 29 , 47 , 48 , 49 , 50 , 51 , 52 ]. The documents which did not report empirical research studies presented discussions based on clinical case examples (n = 6) [ 17 , 18 , 53 , 54 , 55 , 56 ] or provided reviews or opinion pieces (n = 4) [ 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The review identified 31 documents (see Table S1 ) from those 19 papers reporting empirical research, of which 11 used quantitative methods [ 11 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and 8 used qualitative methods [ 13 , 29 , 47 , 48 , 49 , 50 , 51 , 52 ]. The documents which did not report empirical research studies presented discussions based on clinical case examples (n = 6) [ 17 , 18 , 53 , 54 , 55 , 56 ] or provided reviews or opinion pieces (n = 4) [ 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 empirical papers included, a range of study designs and methods were reported (see Figure 2 ). These were primarily interview studies (n = 10) [ 13 , 29 , 37 , 38 , 47 , 48 , 49 , 50 , 51 , 52 ]. Two used a more structured approach to the interviews [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As myopathy progresses to respiratory muscles in IBMPFD, PFTs are useful in monitoring respiratory function following diagnosis as is the case in other disorders such as late onset Pompe disease, ALS, and IBM [7,[20][21][22][23][24]. The general increase in sleep disruptions and remarkable drop in sleep duration over time was noted or will on monitoring him with a Fitbit.…”
Section: Discussionmentioning
confidence: 99%